Effect of yeast (Saccharomyces cerevisiae) associated or not to micro minerals in chemical composition, tissue composition, lipid oxidation and quality of meat of feedlot lambs (Research, Society and Development, 2020)
Growth promoters are increasingly restricted in ruminants’ diet. By the need to find safer alternatives for the environment and meat consumers the yeast in probiotics being an alternative. Chemical and tissue composition, lipid oxidation and sensorial quality of meat lambs supplemented with yeast (Saccharomyces cerevisiae), associated or not with the micro minerals, finished in feedlot was evaluated. 24 male lambs, Texel breed lambs divided into three experimental groups (n = 8 lambs / group) CON (without addition of yeast (Saccharomyces cerevisiae)), PB (constituted by yeast Saccharomyces cerevisiae) and PBM (constituted by yeast Saccharomyces cerevisiae + selenium and chrome). After slaughter of the lambs (mean live weight of 55.1 kg), the carcasses were refrigerated for 24 hours, sectioned in the medium for analysis of the Longissimus lumborum muscle. No significant values (P>0.05) were observed for the most qualitative analyzes, except for fat (%) in the proximate composition, with highest values for PBM (5.62%) when compared to CON and PB (P